The making of a construct: Lessons from 30 years of the Kogut and Singh cultural distance index - CUYPERS, Ilya R. P. (Institutional Knowledge at Singapore Management University, 2018)
The 30-year anniversary of Kogut and Singh’s (1988) groundbreaking study that introduced the concept of cultural distance and its accompanying measure provides the opportunity to take stock of what makes for a good construct. We organize our discussion around the issues of concept, algorithm, and data to clarify and gauge their contribution, before highlighting the impact of their work more generally. Many of the challenges raised by critical observers focus on one of these three dimensions. As there is value in looking systematically at the construct from concept to data, we set out the argument of the index and discuss the validity of selected lines of criticism. We identify a number of emergent and future directions for the conceptualization and measurement of cultural distance, to facilitate the continuing advancement of work on international business. © 2018, Academy of International Business.